E-government services and citizens' satisfaction in the United Arab Emirates: a research agenda - Fauzi, Mohamed; Sabah, Mohamad (Institute of Advanced Scientific Research, 2018)
This paper attempts to identify factors effecting the relationships between the egovernment services, namely DeG Synergetic Services, and citizens’ satisfaction in the United Arab Emirates (UAE). Evaluation of UAE e-government services is very crucial; nevertheless, theory on assessment of e-government is still nascent in terms of development and execution. Previous studies have demonstrated that the objective sought by United Arab Emirates is to achieve utilization of ICT to empower the services to enhance accountability and effectiveness (Alalwany and Alahmari, 2007; Alshawi and Alalwany, 2009). Adoption of e-government initiatives will definitely benefit the government including cost savings and overall citizens’ satisfaction. Hence, analysing the effect of egovernment on citizen’s satisfaction perspective is crucial in justifying investment in egovernment projects. Thus this will help in addressing the e-government mismatched budgetary constraints. This evaluation will furthermore help in uncovering the effectiveness of the current e-government initiatives in the UAE. Hence, the problem researcher deals in this study comprises in assessing relevant factors affecting the citizens’ satisfaction with a variety of e-Government services in the United Arab Emirates, namely DeG synergetic services (DeG). An extensive review of literature has been conducted and a theoretical framework is proposed. This study will be utilizing a quantitative survey design as the basis of analysis.